Banking Supervision and Regulation in Turkey: Basel 1, Basel 2 and Basel 3 - Diallo, Fatoumata Diaraye (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACt: The main objective of this thesis is to consider the preparations undertaken so far by the Turkish Banks to determine the level of preparedness of the Banks for Basel Criteria. This research accesses the transition process of the Turkish banks in implementing Basel 1, 2, and 3 standards: the preparatory work for the international banking regulation and supervision which is a legal regulation in regard to Turkish banking and the steps taken by the local banking regulation and supervision. BRSA is examined and the sector's ability to meet the Basel requirement is evaluated. In addition, the study evaluates the possible effects of the new rigorous capital (Basel 3) on Turkish Financial sector, which are not yet finalized. Many countries have failed to meet the requirements of the first two Basel criterias. However, Turkey was one of the rare countries in which the global financial crisis did not affect its banking sector because of the strong capital base and the capital adequacy ratios (CAR) of banks. The Turkish banking will not face any challenges to implement the third international regulation and supervision on banks. It is considered that Turkish financial sector’s ability to implement to the international rules would be more contributive to the economic growth, sustainable development and structural transformation of the country. In general, also, other structural problems and main macroeconomic instability issues of the Turkish economy will be resolved. Keywords: Basel 1, 2, 3, Capital Adequacy Ratio, Banks, Turkey. ………………………………………………………………………………………………………………………… ÖZ: Bu tezin esas amacı Türk bankalarının Basel Kriteri için hazır olma seviyelerini sağlamak için şimdiye kadar yapılan hazırlıkları göz önünde bulundurmaktır. Bu araştırma Türk bankalarının Basel 1, 2 ve 3 standardlarını uygulamadaki geçiş sürecine giriş yapar: Türk bankacılığı bağlamında yasal bir düzenleme olan uluslararası bankacılık düzenleme ve denetimi için hazırlık çalışmaları ve yerel bankacılık düzenleme ve denetimi tarafından atılan adımlar. BRSA incelenmiş ve sektörün Basel koşulunu yerine getirmedeki becerisi değerlendirilmiştir. Çalışma ayrıca henüz tamamlanmamış olan, Türk Finans sektöründeki yeni sıkı sermayenin (Basel 3) olası etkilerini de değerlendirir. Birçok ülke ilk iki Basel kriterinin koşullarını yerine getirmede başarısız olmuştu. Ancak Türkiye küresel mali krizin bankacılık sektörünü güçlü sermaye tabanı ve bankaların sermaye yeterlilik oranları (CAR) nedeniyle etkilemediği nadir ülkelerden birisidir. Türk bankacılığı bankalar üzerinde üçüncü uluslararası düzenleme ve denetim uygulamasını gerektirecek herhangi bir zorlukla karşılaşmayacaktır. Türk finans sektörünün uluslararası kuralları uygulamadaki becerisinin ekonomik büyüme, sürdürülebilir gelişme ve ülkenin yapısal dönüşümüne daha fazla katkı sağlayabileceği dikkate alınmıştır. Ayrıca genelde Türk ekonomisinin diğer yapısal problemleri ve ana makroekonomik istikrarsızlık konuları çözümlenecektir. Anahtar Kelimeler: Basel 1, 2, 3, Sermaye Yeterlilik Oranı, Bankalar, Türkiye.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2014. Supervisor: Assoc. Prof. Dr. Nesrin Özataç.
Keywords: Banking and Finance; Banks and banking - Law and legislation - Turkey; Basel 1,2,3, Capital Adequacy Ratio, Banks, Turkey